A study on the improvements in reading outcome of EFL learners taking the intensive IELTS exam preparation course at AMES English language center = Nghiên cứu về mức độ tiến bộ với kỹ năng đọc của học viên sau khi tham gia khoa học luyện chứng - Đặng, Thu Hương (2019)
In recent time, there has been an increasing number of those who want to sit an IELTS test to get a desirable score for their academic, recruitment or admission purposes. This has resulted in the fact that many private English language schools in Vietnam have included IELTS preparation courses in their training program. These schools usually state strongly about the effectiveness of their IELTS preparation classes; however, there has been little investigation on this so far.